(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article is about public welfare in Buddhism, the purposes of this study were divided into two issues, 1) to study the background of public welfare in Buddhism 2) to study the scope of the duty of monks’ welfare towards society. The background of public welfare in Buddhism: It occurred from the feeling of people that they were in trouble. In the doctrine of Buddhism, the Lord Buddha said about Buddha’s doctrine that the public welfare could be interpreted as follows; it was the service, happiness for angel (Deva) and humans. It also provided the facilitation of consumer products and created harmony.The scope of the duty of monks’ welfare toward to society was found that there were different perspectives such as Dhamma was a contribution to society by giving Dhamma to have initial, mid and utmost beauty. Discipline (Vinaya Dhamma) was welfare that did not conflict with the discipline and did not have self-dealing. From the point of view of Thai society, there were two views which consisting of agreement and disagreement which had an interesting reason. However, public welfare must merely be for promotion to disseminate the Dhamma